Allogeneic cetuximab-armed gamma delta T cells using antibody-cell conjugation technology for the treatment of EGFR-expressing solid tumors - Yi-Chiu Kuo; Hao-Kang Li; Tai-Sheng Wu; Ying Ru; Chia-Yun Lee; Pei-Ju Leng; Yi-Chun Hsieh; Yun-Jung Chiang; Zih-Fei Cheng; Yan-Liang Lin; Shih-Chia Hsiao; Sai-Wen Tang (Journal for ImmunoTherapy of Cancer, 2025)
Background Targeting epidermal growth factor receptor (EGFR) has become a strategic approach in cancer therapy, using various modalities including chimeric antigen receptor (CAR)-αβT cell therapies. Despite significant advancements in autologous CAR-αβT cell therapies in B-cell lymphoma, current cell therapies face challenges such as potential risks associated with genetic engineering, waiting time and high costs of autologous CAR-αβT cell therapies. Innovations in click chemistry and bioorthogonal chemistry have enabled the development of antibody-cell conjugation (ACC) technology, which links cancer-targeting antibodies to immune cells without genetic modifications, potentially providing a safer profile.Methods In this study, we introduce ACE2016, an innovative allogeneic cell therapy targeting EGFR. ACE2016 is generated by ACC technology to conjugate donor-derived γδ2 T cells with the EGFR-specific antibody cetuximab.Results Our preclinical studies demonstrate that ACE2016 exhibits superior cytotoxicity against various EGFR-expressing cancer cell lines and minimal cytotoxic effects on normal cells. Mechanistic studies revealed that ACE2016 enhances cytotoxicity through increased capacity towards EGFR-expressing cancer cells, enhanced levels of cytotoxic cytokines and recruitment of peripheral cytotoxic cells, reflecting significant tumor suppression and prolonged survival in ACE2016-treated groups without causing treatment-related toxicity in vivo.Conclusions These findings support the clinical potential of ACE2016 as an off-the-shelf γδ2 T-cell therapy for EGFR-expressing cancers, offering a combination of specificity, scalability, and safety in the development of solid tumor therapy.